ANALISIS KEPUASAN KONSUMEN PADA COFFEE FASTE DI KOTA BANDAR LAMPUNG - Rosa Rizki Ramadani; Fibra Nurainy; Teguh Setiawan; Wisnu Satyajaya (Jurusan Teknologi Hasil Pertanian, 2026)
The coffee shop industry in Indonesia has experienced rapid growth along with the increasing coffee consumption culture and changes in people’s lifestyles. This condition also occurred in Bandar Lampung City, which was marked by the emergence of many coffee shops that intensified competition among business actors. This competition required coffee shop businesses to understand consumer needs and expectations in order to maintain customer satisfaction and loyalty. Coffee Faste Signature, as one of the coffee shops in Bandar Lampung City, needed to evaluate the performance of product, price, service, and facility attributes provided to consumers. This study aimed to identify consumer characteristics, analyze the level of importance and performance of service attributes, and analyze consumer satisfaction with product, price, service, and facility attributes at Coffee Faste in Bandar Lampung City. The research was conducted from November to December 2025 and involved 100 respondents determined using the Slovin formula with a 90% confidence level and a 10% margin of error through an accidental sampling technique. The analytical methods used included descriptive analysis, validity and reliability tests, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). The results showed that social media promotion, cleanliness of rooms and equipment, and the availability and function of supporting facilities were positioned in Quadrant I as the main priorities for improvement. The average conformity level reached 101%, indicating that the overall performance of Coffee Faste Signature was categorized as good. The CSI value of 83.59% indicated that consumers were very satisfied with the products, prices, services, and facilities provided.